Students’ Perception On Teacher’s Teaching Reading Through Local Folktale - M. Husni Thamrin; Taufiq Kurniawan (Lembaga Pengembangan Kinerja Dosen, 2023)
Teaching reading to the English learners is an essential skill to teach. It is required a typical way of teaching by selecting such an exciting instructional. Many ways might be used to do. One of them is by using an outstanding local folktale. However, the current reality showed that most of the students’ skill of reading were very low. It was proved by lack of students’ participation when they responded the topic of the lesson taught. In line with this problem, the purpose of this research was to determine the students’ perception on teacher’s teaching reading through local folktale. This research was a descriptive qualitative research. To sum up the finding of obtained data from those instrumets, the use of local folktale in teaching reading was in good response. The open questionaire indicated that there was 13.33% strongly agreed, 33.33% agreed, 27.85 was anxious of the application of local folktale, 20.71% disagreed and 4.76% strongly diagreed. It was also supported by interview result with the respondents. Viewing the overall result, it could be concluded that local folktale was welcomed well by the students as one of straategies to teach reading.